Can Historical Institutionalism Explain the Reforms of the Common Agricultural Policy? - Nicoleta Lăşan (Romanian Journal of European Affairs)
Historical institutionalism, one of the three variants of new institutionalism, has been largely employed by scholars to explain the development of one of the first policies developed at the European level, namely the Common Agricultural Policy (CAP). Due to historical institutionalism’s claim that policies tend to follow the path set at their creation, it is not surprising that it could easily account for the development of the CAP before 1990s since this was one of the most resistant policies set by the member states of the European Union. The main challenge for historical institutionalism is to explain the shifts that occurred in this policy due to the reforms agreed after 1990, reforms that are often mentioned in the literature as being crucial. The aim of this paper is to show that historical institutionalism can accommodate the 1992 and 2003 reforms of the Common Agricultural Policy, and from this we can infer that the changes needed to adapt this policy of the EU to the conditions of an ever enlarging Europe will take place slowly, if at all.